A review of Net Zero Energy Buildings with reflections on the Australian context - Wells, Louise; Rismanchi, Behzad; Aye, Lu (Energy and buildings, 2018)
A Net Zero Energy Building (NZEB) is a term, subject to ambiguity, that could be used to describe a building with characteristics such as equal energy generation to usage, significantly reduced energy demands, energy costs equalling zero or net zero greenhouse gas (GHG) emissions. Despite lacking an authoritative definition of NZEBs, this relatively new emerging concept in Australia provides significant opportunities to reduce GHG emissions, energy usage and operational energy costs for buildings owners. This paper aims to explore the existing NZEB models, assess the progression of NZEB literature, identify key policies encouraging NZEB development and recognise potential areas of NZEB research.